The future of Irish access transport : investigation, modelling and appraisal - Whitney, Warren James (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2002)
This thesis aims to examine in detail a variety of possible strategies for the development of the Irish access transport system. The Irish access transport system is considered as being the system (passenger and freight) linking the island of Ireland (Northern Ireland and the Republic of Ireland) with Great Britain and the remainder of the European Union. Specific aims of the research project include: -- To examine possible alternative strategies for the development of the Irish access transport system up to the year 2020, with an important sub-objective in this regard of investigating technological and other measures which might form part of such strategies. -- To develop a means of predicting future transport demand under alternative strategies. -- To develop an appraisal framework allowing the comparison of different strategy options. A number of alternative future strategies for the transport system were developed by reviewing available technological and other measures, identifying those appearing most promising, developing these latter in greater detail and combining them into consistent strategies. A future background scenario, embracing population and economic developments in the period to 2020 and forming the basis against which the strategies were assessed, was developed with reference to available information and current projections.
Keywords: Civil Engineering, Ph.D.; Ph.D. Trinity College Dublin